Olahan Ikan Lele Menjadi Stik Lele Sebagai Sumber Pendapatan Lain Kelompok PKK Olahan Ikan Lele Kelurahan Plaju Darat Kota Palembang - Sisvaberti Afriyatna; Idealistuti; Mustopa Marli Batubara; Rahidin H Anang; Alhanannasir Alhanannasir; Suyatno Suyatno; Mukhtarudin Muchsiri (Altifani Journal: International Journal of Community Engagement, 2026)
Catfish is a freshwater fishery commodity with significant production levels across various regions, including Plaju Darat Urban Village in Palembang City. Currently, the utilization of catfish is generally limited to simple preparations, such as frying or serving it as a standard daily side dish. However, catfish possesses high nutritional value—particularly protein—making it an excellent candidate for development into various processed food products. One viable strategy is product diversification: processing catfish into snacks like catfish sticks, which offer greater consumer appeal, a longer shelf life, and higher economic value. This community service initiative was conducted to empower the local community, specifically the members of the PKK (Family Welfare Empowerment) group in Plaju Darat. The activity took place at the Plaju Darat Urban Village Office meeting room in Plaju District, Palembang City, in December 2025, with 22 PKK members participating. A group-based approach was employed for the outreach and training. Prior to the activity, most participants were unaware that catfish meat could be processed into various products, such as catfish sticks. The results demonstrated the activity's success, with participants' knowledge increasing by up to 95% based on pre-test and post-test scores. Participants gained insight into the potential of diversifying catfish products into sticks—a value-added item based on local food resources—and acquired the understanding and practical skills needed to produce them.